Comparative transcriptomics reveals the role of altered energy metabolism in the establishment of single-cell C4 photosynthesis in Bienertia sinuspersici - Han, Sang-Yun; Kim, Woe-Yeon; Kim, Jung Sun; Hwang, Inhwan (Frontiers in Plant Science, 2023)
Single-cell C4 photosynthesis (SCC4) in terrestrial plants without Kranz anatomy involves three steps: initial CO2 fixation in the cytosol, CO2 release in mitochondria, and a second CO2 fixation in central chloroplasts. Here, we investigated how the large number of mechanisms underlying these processes, which occur in three different compartments, are orchestrated in a coordinated manner to establish the C4 pathway in Bienertia sinuspersici, a SCC4 plant. Leaves were subjected to transcriptome analysis at three different developmental stages. Functional enrichment analysis revealed that SCC4 cycle genes are coexpressed with genes regulating cyclic electron flow and amino/organic acid metabolism, two key processes required for the production of energy molecules in C3 plants. Comparative gene expression profiling of B. sinuspersici and three other species (Suaeda aralocaspica, Amaranthus hypochondriacus, and Arabidopsis thaliana) showed that the direction of metabolic flux was determined via an alteration in energy supply in peripheral chloroplasts and mitochondria via regulation of gene expression in the direction of the C4 cycle. Based on these results, we propose that the redox homeostasis of energy molecules via energy metabolism regulation is key to the establishment of the SCC4 pathway in B. sinuspersici.